Rancang Bangun Sistem Informasi Bank Sampah Gajah Putih (Sibasti) Karangasem Surakarta - Puspitasari, Norma; Susanto, Edy; Rejeki, Sri (Politeknik Indonusa Surakarta, 2021)
Gajah Putih Garbage Bank, Karangasem Surakarta, currently requires a system to manage the results of depositing waste by customers and a website that can make the Gajah Putih Garbage Bank better known to the wider community so that they can sell their products to the public. The management of waste deposit right now is still manual and not computerized properly and the products produced by the waste bank are not well known to the general public so that this makes the management of customer deposits an error and the products from the waste bank are not sold optimally. The purpose of this system is to make it easier for customers to computerize waste deposit management and so that the Gajah Putih Garbage Bank is better known by the wider community so that it can market its products optimally. The method used is the waterfall method. The results of the system created are in the form of a website with a view of the legality of the Gajah Putih Garbage Bank, the display of the input process and output menus that are well-designed in order to facilitate the management of depositing waste and marketing the products of the waste bank.